Mechanical response of 3D Insert® PCL to compression. (January 2017) - Brunelli, M.; Perrault, C.M.; Lacroix, D.
Abstract: 3D polymeric scaffolds are increasingly used for in vitro experiments aiming to mimic the environment found in vivo, to support for cellular growth and to induce differentiation through the application of external mechanical cues. In research, experimental results must be shown to be reproducible to be claimed as valid and the first clause to ensure consistency is to provide identical initial experimental conditions between trials. As a matter of fact, 3D structures fabricated in batch are supposed to present a highly reproducible geometry and consequently, to give the same bulk response to mechanical forces. This study aims to measure the overall mechanical response to compression of commercially available 3D Insert PCL scaffolds (3D PCL) fabricated in series by fuse deposition and evaluate how small changes in the architecture of scaffolds affect the mechanical response. The apparent elastic modulus (Ea) was evaluated by performing quasi-static mechanical tests at various temperatures showing a decrease in material stiffness from 5 MPa at 25 °C to 2.2 MPa at 37 °C. Then, a variability analysis revealed variations in Ea related to the repositioning of the sample into the testing machine, but also consistent differences comparing different scaffolds. To clarify the source of the differences measured in the mechanical response, the same scaffolds previously undergoing compression, were scanned by micro computed tomography (μCT) to identify any architectural difference. Eventually, to clarify the contribution given by differences in the architecture to the standard deviation of Ea, their mechanical response was qualitatively compared to a compact reference material such as polydimethylsiloxane (PDMS). This study links the geometry, architecture and mechanical response to compression of 3D PCL scaffolds and shows the importance of controlling such parameters in the manufacturing process to obtain scaffolds that can be used in vitro or in vivo under reproducible conditions. Graphical abstract: Highlights: 3D PCL responded linearly to compression for strains between 1 and 2.5%. Plastic deformation of 3D PCL was prevented applying compressive strains below 8%. A statistical analysis revealed a variability up to 30% in the mechanical response.